Autophagy and the primary cilium in cell metabolism: What’s upstream? - Claude-Taupin, Aurore; Dupont, Nicolas; Codogno, Patrice (Frontiers in Cell and Developmental Biology, 2022)
The maintenance of cellular homeostasis in response to extracellular stimuli, i.e., nutrient and hormone signaling, hypoxia, or mechanical forces by autophagy, is vital for the health of various tissues. The primary cilium (PC) is a microtubule-based sensory organelle that regulates the integration of several extracellular stimuli. Over the past decade, an interconnection between autophagy and PC has begun to be revealed. Indeed, the PC regulates autophagy and in turn, a selective form of autophagy called ciliophagy contributes to the regulation of ciliogenesis. Moreover, the PC regulates both mitochondrial biogenesis and lipophagy to produce free fatty acids. These two pathways converge to activate oxidative phosphorylation and produce ATP, which is mandatory for cell metabolism and membrane transport. The autophagy-dependent production of energy is fully efficient when the PC senses shear stress induced by fluid flow. In this review, we discuss the cross-talk between autophagy, the PC and physical forces in the regulation of cell biology and physiology.